2022
DOI: 10.3390/pr10061052
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Model for the Prediction of Methane Bi-Reforming Products Using CO2 and Steam

Abstract: The bi-reforming of methane (BRM) is a promising process which converts greenhouse gases to syngas with a flexible H2/CO ratio. As there are many factors that affect this process, the coupled effects of multi-parameters on the BRM product are investigated based on Gibbs free energy minimization. Establishing a reliable model is the foundation of process optimization. When three input parameters are changed simultaneously, the resulting BRM products are used as the dataset to train three artificial neural netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Taherdangkoo et al [12] demonstrated the application of machine learning algorithms, including boosted regression trees optimized with Bayesian optimization, to accurately predict CH4 solubility in water and seawater across a range of temperatures and pressures, achieving a high coefficient of determination (R 2 = 0.99). Deng and Guo [13] developed an artificial neural network model to predict the products of CH4 bi-reforming using CO2 and steam, demonstrating its accuracy with correlation coefficients over 0.995 across various operational conditions. Li et al [14] developed two neural network models to predict CO2 solubility in aqueous blended amine solvents, using extensive experimental data and a backpropagation learning algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Taherdangkoo et al [12] demonstrated the application of machine learning algorithms, including boosted regression trees optimized with Bayesian optimization, to accurately predict CH4 solubility in water and seawater across a range of temperatures and pressures, achieving a high coefficient of determination (R 2 = 0.99). Deng and Guo [13] developed an artificial neural network model to predict the products of CH4 bi-reforming using CO2 and steam, demonstrating its accuracy with correlation coefficients over 0.995 across various operational conditions. Li et al [14] developed two neural network models to predict CO2 solubility in aqueous blended amine solvents, using extensive experimental data and a backpropagation learning algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Over the catalyst surface, metal sintering is caused by a high operating temperature, while coke is formed and grown via side reactions, methane cracking (Equation (2)), and the Boudouard reaction (Equation (3)). Moreover, the side reaction that consumes H 2 and causes the low H 2 /CO ratio in the syngas product is the reverse water–gas shift (RWGS, Equation (4)) [ 10 , 11 ]. CH 4 + CO 2 → 2H 2 + 2CO △H o 298 K = +247 kJ/mol CH 4 → 2H 2 + C △H o 298 K = +75 kJ/mol 2CO → CO 2 + C △H o 298 K = +173 kJ/mol H 2 + CO 2 → H 2 O + CO △H o 298 K = +41 kJ/mol …”
Section: Introductionmentioning
confidence: 99%
“…For the Ni/Al 2 O 3 parent, zirconium oxide (ZrO 2 ) was examined as an effective structural and electronic promoter. In addition, ZrO 2 provides the great mechanical strength and high thermal stability. Meanwhile, ZrO 2 creates the oxygen mobility from redox properties and presents high Lewis basicity. Our previous work studied a ZrO 2 -promoted Ni-based catalyst for CSCRM. ZrO 2 enhances H 2 production by promoting the steam adsorption-dissociation via oxygen vacancies .…”
Section: Introductionmentioning
confidence: 99%
“…Coke majorly formed via the Boudouard reaction (eq ) and CH 4 decomposition (eq ). , 2 CO ( g ) normalC ( s ) + CO 2 ( g ) , normalΔ H 298 ° = prefix− 173 0.25em kJ / mol CH 4 ( g ) normalC ( s ) + 2 H 2 ( g ) , normalΔ H 298 ° = prefix+ 75 0.25em kJ / mol …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation